Flipped Classroom in Teacher Education: A Scoping Review - Han, Han; Røkenes, Fredrik Mørk (Frontiers in Education, 2020)
Although flipped classroom (FC) has been popular in education since the 2000s, there is a lack of reviews on how the teaching approach has been applied and what has been gained in the field of teacher education. Most reviews focus either on implementation and learning outcomes with students in higher education and disciplines other than education, or on the latter approaches with primary and secondary school pupils. This article presents a scoping literature review of 33 studies published between 2014 until 2019 on flipped classroom (FC) in teacher education. Our analysis points out that studies were mainly conducted in the United States, with an increased implementation in European and Asian countries, and with adoption primarily in the disciplines pedagogy, science, and language arts. Moreover, a majority of studies employed mixed methods with surveys being the most commonly used instrument to collect data. Two main foci were identified across the reviewed studies: student perceptions and academic performance. The analysis of the former revealed six outcomes (1. Attitude, motivation, and emotion; 2. Content delivery; 3. Learning environment; 4. Learning experience; 5. Instructor and student presence; 6. Engagement). Based on our synthesis, we discuss current trends and future development in the research field, FC’s pedagogical value added in teacher education, potential knowledge gaps in the research literature.